2000
DOI: 10.1128/mcb.20.11.3896-3905.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Effects of pp120 (Ceacam 1) on the Mitogenic Action of Insulin and Insulin-Like Growth Factor 1 Are Regulated by the Nonconserved Tyrosine 1316 in the Insulin Receptor

Abstract: pp120 (Ceacam 1) undergoes ligand-stimulated phosphorylation by the insulin receptor, but not by the insulin-like growth factor 1 receptor (IGF-1R). This differential phosphorylation is regulated by the C terminus of the ␤-subunit of the insulin receptor, the least conserved domain of the two receptors. In the present studies, deletion and site-directed mutagenesis in stably transfected hepatocytes derived from insulin receptor knockout mice (IR ؊/؊ ) revealed that Tyr 1316 , which is replaced by the nonphosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 67 publications
(79 reference statements)
2
27
0
Order By: Relevance
“…Najjar and coworkers identified pp120, a plasma membrane glycoprotein, as a specific substrate for the IR but not the IGF-IR (Najjar et al, 1997;Soni et al, 2000). Phosphorylation of pp120 is required for its function in insulin endocytosis (Formisano et al, 1995), and also for its inhibitory effect on the mitogenic actions of insulin (Soni et al, 2000).…”
Section: Receptor Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Najjar and coworkers identified pp120, a plasma membrane glycoprotein, as a specific substrate for the IR but not the IGF-IR (Najjar et al, 1997;Soni et al, 2000). Phosphorylation of pp120 is required for its function in insulin endocytosis (Formisano et al, 1995), and also for its inhibitory effect on the mitogenic actions of insulin (Soni et al, 2000).…”
Section: Receptor Functioningmentioning
confidence: 99%
“…Phosphorylation of pp120 is required for its function in insulin endocytosis (Formisano et al, 1995), and also for its inhibitory effect on the mitogenic actions of insulin (Soni et al, 2000). Interestingly, when the carboxyl terminus of the IGF-IR is replaced by an equivalent region of the IR, the chimeric IGF-IR can then bind to and phosphorylate pp120, and the effect of IGF-I on cell growth is decreased (Soni et al, 2000). Mutation of Tyr 1316 in the IR, which is not conserved in the IGF-IR, abrogates the insulininduced tyrosine phosphorylation of pp120 and its ability to suppress insulin-induced mitogenesis.…”
Section: Receptor Functioningmentioning
confidence: 99%
“…Phosphorylation of pp120 is required for its function in insulin endocytosis (Formisano et al, 1995), bile acid transport (Sippel et al, 1994), tumor suppression (Kleinerman et al, 1995), and its inhibitory effect on the mitogenic actions of insulin (Soni et al, 2000). Interestingly, when the carboxyl-terminus of the IGF-1R is replaced by an equivalent region of the IR, the chimeric IGF-1R then can bind to and phosphorylate pp120, decreasing its effect on cell growth (Soni et al, 2000). Mutation of the tyr 1316 in the IR, which is not conserved in the IGF-1R, abrogates the insulin-induced tyrosine phosphorylation of pp120 and its ability to suppress the mitogenic action of insulin (Soni et al, 2000).…”
Section: Proximal Substratesmentioning
confidence: 99%
“…Najjar and coworkers identified pp120, a plasma membrane glycoprotein, which is a substrate for the IR but not for the IGF-1R (Najjar et al, 1997;Soni et al, 2000). Phosphorylation of pp120 is required for its function in insulin endocytosis (Formisano et al, 1995), bile acid transport (Sippel et al, 1994), tumor suppression (Kleinerman et al, 1995), and its inhibitory effect on the mitogenic actions of insulin (Soni et al, 2000). Interestingly, when the carboxyl-terminus of the IGF-1R is replaced by an equivalent region of the IR, the chimeric IGF-1R then can bind to and phosphorylate pp120, decreasing its effect on cell growth (Soni et al, 2000).…”
Section: Proximal Substratesmentioning
confidence: 99%
“…The biological actions of IGFs are thought to be mediated through interaction with IGF-1R. Previous studies have indicated the presence of IGF-1R on the hepatocyte cell surface (Soni et al, 2000;Froesch et al, 1985;Caro et al, 1988). But the IGF-1 signal transduction pathways in primary hepatocytes have not been well studied.…”
Section: Discussionmentioning
confidence: 99%